2014
DOI: 10.1038/nn.3721
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of mitochondrial protein import by mutant huntingtin

Abstract: Mitochondrial dysfunction is associated with neuronal loss in Huntington’s disease (HD), a neurodegenerative disease caused by an abnormal polyglutamine expansion in huntingtin (Htt). However, the mechanisms linking mutant Htt and mitochondrial dysfunction in HD remain unknown. We identify an interaction between mutant Htt and the TIM23 mitochondrial protein import complex. Remarkably, recombinant mutant Htt directly inhibited mitochondrial protein import in vitro. Furthermore, mitochondria from brain synaptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
194
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(213 citation statements)
references
References 53 publications
15
194
0
1
Order By: Relevance
“…It was recently shown that mitochondrial protein import is inhibited by mHtt leading to neuronal death [97]. Here we show that mitochondrial levels of Tom20 and Tom40 are significantly enhanced by insulin in HD striatal cells, suggesting that the peptide may promote increased recognition, movement and import of cytosolically synthesized mitochondrial proteins.…”
Section: Discussionmentioning
confidence: 52%
“…It was recently shown that mitochondrial protein import is inhibited by mHtt leading to neuronal death [97]. Here we show that mitochondrial levels of Tom20 and Tom40 are significantly enhanced by insulin in HD striatal cells, suggesting that the peptide may promote increased recognition, movement and import of cytosolically synthesized mitochondrial proteins.…”
Section: Discussionmentioning
confidence: 52%
“…It was recently reported that mHtt inhibits protein import into mitochondria in vitro (isolated mouse forebrain mitochondria and HdhQ111 striatal cell line) and in vivo (R6/2 mice) (Jonas, 2014;Yano et al, 2014). Using immunoprecipitation and TIM23 overexpression experiments, the authors suggest that mitochondrial protein import is inhibited by the direct interaction of mHtt with the TIM23 complex (Yano et al, 2014) (Fig.…”
Section: Mitochondrial Biogenesismentioning
confidence: 98%
“…Using immunoprecipitation and TIM23 overexpression experiments, the authors suggest that mitochondrial protein import is inhibited by the direct interaction of mHtt with the TIM23 complex (Yano et al, 2014) (Fig. 1B).…”
Section: Mitochondrial Biogenesismentioning
confidence: 99%
“…Although the functional relationship of Htt to mitochondria is still uncertain [21], it is becoming increasingly apparent that mHtt can impair mitochondrial function directly [22]. Moreover, available data indicate that mitochondrial defects may initiate the disease onset [23][24][25][26][27][28][29][30][31].…”
Section: Huntington's Diseasementioning
confidence: 99%